Thrombin Production, Inactivation and Expression during Open Heart Surgery Measured by Assays for Activation Fragments Including a New ELISA for Prothrombin Fragment F1+2 - Boisclair, Michael D; Lane, David A; Philippou, Helen; Sheikh, Sajila; Hunt, Beverley (Thrombosis and Haemostasis, 1993)
Activation of coagulation was studied during the peri-operative period in patients undergoing cardiopulmonary bypass (CPB) surgery using activation markers which have recently become available: prothrombin fragment F1 + 2 (F1 + 2), which is a measure of total thrombin generation, and thrombin-antithrombin complex, which is a measure of inactivation of free thrombin by antithrombin. Levels of the specific marker of fibrin breakdown, D-dimer, were also determined. F1 + 2 levels were assessed using a newly developed ELISA described herein which employs a neoantigen-specific capture antibody raised using a synthetic peptide; the latter antibody has been pre-adsorbed against prothrombin to ensure high specificity for F1 + 2.Increased generation of thrombin during surgery was clearly demonstrated despite maintenance of a high concentration of heparin during the period of extracorporeal blood circulation. There was a close association (r = 0.882) between the generation of thrombin (F1 + 2 levels) and its inhibition (TAT levels). Differences were noted, however, between the information provided by F1 + 2 and TAT, which are interpreted with regard to the different in vivo fates of F1 + 2 and thrombin. The enhanced activation and inhibition of coagulation observed during CPB was suppressed once physiological blood circulation was restored, with F1 + 2 returning to pre-surgical levels within 24 h after surgery. During the post-operative period D-dimer levels, which rose in concert with F1 + 2 and TAT levels, remained highly elevated, suggesting that not all of the generated thrombin was inactivated by antithrombin. It is concluded that heparin is only partially effective as an anticoagulant during CPB surgery. F1 + 2 is an unambiguous marker of thrombin generation and its measurement may be a useful means of evaluating more effective coagulation inhibitors in CPB.